2008
DOI: 10.1055/s-2007-965771
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Atresia of the Small Intestine: A 20-Year Review

Abstract: Clinical observations of sporadic cases of MIA confined to the small bowel lend support to the hypothesis of a vascular incident etiology. One-stage restoration of intestinal continuity with preservation of maximal intestinal length should be the basic principle of any operative management of MIA. Despite a relatively high morbidity related to the primary damage of the fetal intestine, excellent results with 100 % survival rates can be obtained. After taking the differences in pathogenesis, anatomical and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A retrospective analysis of 26 cases of multiple intestinal atresias during 20 years by Baglaj et al [1] showed no significant association with other congenital malformations. The only congenital intestinal anomaly that has been associated with intestinal atresia in the literature is Meckel diverticulum [7,8].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A retrospective analysis of 26 cases of multiple intestinal atresias during 20 years by Baglaj et al [1] showed no significant association with other congenital malformations. The only congenital intestinal anomaly that has been associated with intestinal atresia in the literature is Meckel diverticulum [7,8].…”
Section: Discussionmentioning
confidence: 95%
“…The only congenital intestinal anomaly that has been associated with intestinal atresia in the literature is Meckel diverticulum [7,8]. Similar to patients with single atresia, infants with multiple intestinal atresias present with typical symptoms of intestinal obstruction [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, MINAT is sometimes associated with either mild or severe combined immunodeficiency (SCID, MIM: 601457); this combination is invariably lethal (Ali et al, 2011;Shorter et al, 2006). Although the nonhereditary form is thought to derive from vascular disruption, there have been reports of non-hereditary cases, suggesting a hereditary form of MINAT is a consequence of a malformative process of the gastrointestinal tract rather than a vascular anomaly (Baglaj et al, 2008;Puri and Fujimoto, 1988). Mutation in the tetratricopeptide repeat domaine7A (TTC7A MIM: 243150) has been shown to cause the hereditary form of MINAT (Bigorgne et al, 2014;Chen et al, 2013;Samuels et al, 2013).…”
Section: Multiple Intestinal Atresiamentioning
confidence: 99%